Peningkatan Kompetensi Pendidik dalam Menyusun RPP melalui Supervisi Akademik pada MI se-Kecamatan Paliyan Gunungkidul - Purwata Purwata (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2017)
Abstract The learning process in fact directed to membelajarkan students in order to achieve the objectives that have been determined. These goals can succeed in everything related to the learning process are arranged in advance in Learning implementation plan (RPP). This school action research aims to improve the competence of educators in drawing up the implementation plan (RPP) Learning through academic supervision. This research includes research actions are realized in the cycle. Each cycle has always been through four stages: 1) action plan implementation, 2), 3) obeservasi, or 4) observations, and reflections. The subject of this study 23 people educators MI se-Sub Paliyan, Gunungkidul. Technique of data analysis performed with diskriptif analysis. The results of the analysis showed that the competence of educators-educators MI in drawing up the RPP held increased after coaching by supervisors through academic supervision. On the initial observations (pre cycle) obtained an average score of 53.9% (less). After held coaching at 1st cycle of obtaining an average score of 68.7%. Construction resumed in the second cycle, and obtained an average score of 81%. Because it has been a significant increase in competence occurs on Small-scale se-MI educators Subdistrict Paliyan, then there needs to be continued construction in the 3rd cycle. Finally it can be concluded that the school's action research related to the improvement of the competence of educators in drawing up the RPP on the Small-scale Sub se-MI Paliyan through academic supervision can be increased. Keywords: Competence Of Teacher, The Plan Of Implementation Of The Learning, Academic Supervision Abstrak Proses pembelajaran pada hakikatnya diarahkan untuk membelajarkan siswa agar dapat mencapai tujuan yang telah ditentukan. Tujuan tersebut bisa berhasil apabila segala sesuatu yang berhubungan dengan proses pembelajaran disusun terlebih dahulu dalam Rencana Pelaksanaan Pembelajaran (RPP). Penelitian tindakan sekolah ini bertujuan untuk meningkatkan kompetensi pendidik dalam menyusun Rencana Pelaksanaan Pembelajaran (RPP) melalui supervisi akademik. Penelitian ini termasuk penelitian tindakan yang diwujudkan dalam siklus. Setiap siklus selalu melalui empat tahapan: 1) rencana tindakan, 2) pelaksanaan, 3) obeservasi atau pengamatan, dan 4) refleksi. Subjek penelitian ini 23 orang pendidik MI se-Kecamatan Paliyan, Gunungkidul. Teknik analisis data dilakukan dengan analisis diskriptif. Hasil analisis menunjukkan bahwa kompetensi pendidik-pendidik MI dalam menyusun RPP meningkat setelah diadakan pembinaan oleh pengawas melalui supervisi akademik. Pada pengamatan awal (pra siklus) diperoleh skor rata-rata 53,9% (kurang). Setelah diadakan pembinaan pada siklus ke-1 perolehan skor rata-rata 68,7%. Pembinaan dilanjutkan pada siklus ke-2, dan diperoleh skor rata-rata 81%. Karena telah terjadi peningkatan kompetensi yang signifikan pada pendidik MI Binaan se-Kecamatan Paliyan, maka tidak perlu dilanjutkan pembinaan pada siklus ke-3. Akhirnya dapat disimpulkan bahwa penelitian tindakan sekolah yang terkait dengan peningkatan kompetensi pendidik dalam menyusun RPP pada MI Binaan se-Kecamatan Paliyan melalui supervisi akademik dapat meningkat. Kata Kunci: Kompetensi Pendidik, Rencana Pelaksanaan Pembelajaran, Supervisi Akademik